Chronic activation of AMP-activated protein kinase prevents 20-hydroxyeicosatetraenoic acid-induced endothelial dysfunction - Ward, Natalie; Chen, K.; Li, C.; Croft, K.; Keaney, J. (2011)
20-Hydroxyeicosatetraenoic acid (20-HETE) is a potent vasoconstrictor involved in vascular dysfunction and blood pressure regulation. Studies have revealed strong associations between 20-HETE and endothelial dysfunction; however, the signalling mechanisms are largely unknown. Therefore, the aim of the present study was to investigate the effect of 20-HETE on the association between endothelial nitric oxide synthase (eNOS) and heat shock protein 90 (Hsp90). In mouse aortic rings, 20-HETE significantly enhanced the constriction to phenylephrine and inhibited the relaxation to acetylcholine (P = 0.05 vs control rings). In mice with chronic AMP-activated protein kinase (AMPK) activation, this protected against the negative effects of 20-HETE (P < 0.05). Immunoprecipitation of eNOS in human umbilical vein endothelial cells treated with 20-HETE revealed a decrease in basal and vascular endothelial growth factor-stimulated Hsp90 association with eNOS (P < 0.05). Pretreatment of cells with 5′-aminoimidazole-4-carboxyamide-ribonucleoside (AICAR; a chronic activator of AMPK) prevented the loss of Hsp90 association with eNOS following 20-HETE treatment. Treatment with 20-HETE for 24 h induced an increase in eNOS phosphorylation that was not seen following acute treatment (30 min). The increased eNOS phosphorylation was accompanied by transient changes in Akt phosphorylation. In conclusion, 20-HETE impairs eNOS–Hsp90 association, which can be reversed by chronic activation of AMPK. This provides a mechanism for reduced nitric oxide bioactivity and endothelial dysfunction in diseases with elevated 20-HETE levels, such as hypertension.